Metode Kisah Berbasis Audio Visual guna Memperkuat Hasil Belajar dan Perilaku Islami Siswa - M. Dzikrul Hakim Al Ghozali; Lingga Radyca Putri Dynanty (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
The use of audiovisual storytelling methods in Aqidah al-Akhlak instruction remains relatively limited, even though this method is considered to have the potential to enhance students’ understanding of religious concepts and Islamic behavior. This study aimed to examine the impact of using an audiovisual storytelling method on improving Aqidah al-Akhlak learning outcomes and students’ Islamic behavior. The research employed a one-group experimental design with a one-group pretest–posttest model, involving a sample of 20 eighth-grade students at MTs Sinan Gunung Jati Kadu determined through random participant selection. Data were collected through pretests and posttests of learning outcomes and an Islamic behavior questionnaire, then analyzed using normality tests, homogeneity tests, and t-tests. The findings indicate a significant increase in students’ academic achievement and Islamic behavior following the implementation of the audiovisual storytelling method (sig. 0.001 < 0.05), suggesting that this method has a positive and substantive effect on students’ religious understanding and behavior. The study concludes that the audiovisual storytelling method is an effective instructional strategy for improving Aqidah al-Akhlak learning outcomes while simultaneously fostering Islamic behavior. Theoretically, these findings contribute to enriching the literature on the use of instructional media in religious education, whereas practically they recommend the integration of audiovisual storytelling methods into the curriculum to strengthen character and spiritual education. Further studies are recommended to explore the long-term sustainability of behavioral changes and the role of moderating factors, such as students’ behavioral characteristics and teachers’ pedagogical competence.